Lycopene and Red Palm Oil Effects on Hypoglycemics and Antioxidant in Streptozotocin-Induced Diabetic Rats - Ebadi, Seyed Morteza (2011)
Diabetes mellitus is found to be associated with oxidative damage which co-exists with a reduction in the antioxidant status and many contribute to the pathogenesis of type 2 diabetes by increasing insulin resistance or impairing insulin section. The objective of this study was to verify the potential hypoglycemic and antioxidant enzymes activities in streptozotocin-induced diabetic rats and to determine free radical scavenging capacity of lycopene and red palm oil. Lycopene and red palm oil of two dosages (10 and 20 mg/kg body weight) were administered to streptozotocin induced diabetic rats. The rats were force-fed with the supplements once daily for six weeks. For induction of diabetes to rats injected 55 mg/kg body weight of STZ (Streptozotocin) dissolved in 0.05 M citrate buffer (pH4.5). compared to the normal group, the treatment of rats with a single dose of STZ revealed a significant decrease (p<0.05) in total antioxidant status (TAS), activity of antioxidant enzymes catalase (CAT) and superoxide dismutase (SOD), plasma insulin level and body weight. The results of this study showed that red palm oil had higher scavenging activity as compared to lycopene. After six weeks of treatment, threats treated with lycopene and red palm oil at both dosages (10 and 20mg/kg body weight) have lower fasting glucose levels (27.7% reduction in lycopene 10 mg/kg bw; 34.5% in lycopene 20 mg/ kg bw; 32.3% in red palm oil 10 mg/kg bw; 28.4% in red palm oil 20 mg/kg bw) compared to the baseline. SOD activities were found to be significantly (p<0.05) elevated in diabetic groups treated (21% elevation in lycopene 10 mg/kg bw; 37% in lycopene 20mg/kg bw) as compared to the baseline. CAT activities were found to significantly (p<0.05) increased in diabetic groups treated (21% elevation in lycopene 10 mg/ kg bw; 37% in lycopene 20 mg/kg bw; 33.8% in red palm oil mg/kg bw; 35.9% in red palm oil 20 mg/kg bw) as compared to pre-treatment. The lycopene and red palm oil at both dosages showed increase in total antioxidant status (25% increase in lycopene 10 mg/kg bw ; 31% in lycopene 20 mg/kg bw ; 26 % in red palm oil 10 mg /kg bw; 31% in lycopene 20 mg /kg bw) after six weeks administration as compared to baseline. Insulin level increased in treated groups with lycopene and red palm oil at both dosages (36% increase inlycopene 10 mg/kg bw; 52% in lycopene 20 mg /kg bw; 40.61% in red palm oil 10 mg/kg bw; 61.6% in red palm oil 20 mg/kg bw) as compared to pre-treatment. The administration of lycopene and red palm oil administration in diabetic treated rats. The data of this investigation exhibited that lycopene and red palm oil might possess hypoglycemic activity. These findings suggest that lycopene and red palm oil may have substantial therapeutic potentials as an antioxidant in diabetes mellitus that increase total antioxidant status. Therefore, lycopene and red palm oil possesses antioxidant properties which work against the oxidative damage in diabetic subjects. These findings indicate antidiabetic capability of lycopene and red palm oil.